Employee engagement in the South African financial sector - Gounden, Gregory (My University, 2017)
Employee engagement refers to the intrinsic and extrinsic factors that influence motivation and enthusiasm of staff with which they conduct their daily duties. The core focus of this research was based on the psychological conditions and organisational factors influencing employee engagement. The South African financial sector is a service based industry which is highly regulated and labour intensive. It is a mass employer which provides a critical service to the South African population, has a high influence to the global perception of the country and its’ success in this market has a direct effect on the national economy. Employees interact with customers daily and as such, represent the organisation whilst conducting the daily functions. The morale and motivation of staff is reflected in how they perform their activities and leads to either building or breaking the brand equity of the business. Studies show that the general level of employee engagement in South Africa is low. The influencers on employee engagement vary and are driven from a personal point of view. Managers must understand that their employee engagement drivers are not always the same as that of general staff. A qualitative analysis was undertaken to gain an in-depth understanding of the individual perceptions of employee engagement factors of managers and general staff of two different departments within the financial service provider. Face–to-face interviews offered the opportunity to discuss the relevance of employee engagement aspects on an individual level. The results were then collated and analysed. All respondents indicated that their level of engagement at the workplace was high however each person identified several aspects of improvement during the discussions. The key findings identified were that there was a significant difference in the factors that influenced employee engagement in managers versus that of general staff. Managers were influenced by job meaningfulness, iii business culture and alignment of personal and business values whilst general staff focused on fostering their self-efficacy, training and development and work life balance. The proposition factors were however, intertwined with each other linking psychological factors and organisational factors. In order to foster effective employee engagement, combinations of interventions are required. Staff unequivocally identified traits of a transformational leader as the ideal leadership or managerial model for facilitating employee engagement. The financial institution requires appropriate strategic initiatives for fostering employee engagement. Due to the large volume of employees, the individuals’ need for fostering employee engagement can vastly vary. Misinterpretation of the employees needs can result in wasteful expenditure, reduced profit margins and employee disengagement. By understanding the needs of staff and understanding the combinations of interventions required, the large institution is more appropriately empowered to drive effective solutions for fostering employee engagement.
MBA(Thesis)
Keywords: Employee motivation -- South Africa. Financial services industry -- South Africa.